Breeding Performance and Foraging Plasticity of Purple Sunbird (Cinnyris asiaticus) in Crop fields of Northwestern India - Sharma, Pratibha; Sekhon, G. S.; Kaur, Navdeep; Kler, Tejdeep (International Journal of Bio-resource and Stress Management, 2026)
Fieldwork was conducted from February, 2022 to September, 2024 at four rural locations-Aittiana and Halwara in district Ludhiana, Punjab, and Ahmadpur and Mirpur in district Sirsa, Haryana, India representing heterogeneous crop fields interspersed with trees and human structures. The breeding performance and foraging plasticity of the Purple Sunbird (Cinnyris asiaticus) was studied in crop fields of northwestern India, emphasizing its ecological significance within agro-ecosystems. Breeding activities were monitored through point count and focal nest observations to document nesting chronology, site selection, clutch characteristics and breeding parameters. The species utilized a wide spectrum of nesting substrates, including Acacia, Zizyphus, Morus, Punica and artificial supports such as fencing wires, demonstrating strong adaptability to human-modified habitats. A pronounced dietary shift was observed during the breeding period, with adults relying heavily on insects-ants, bees, wasps, spiders, grasshoppers, and termites-for provisioning nestlings, while nectar remained a supplementary resource. Marked inter-annual and inter-site variation was recorded in the onset of nesting, egg-laying, and hatching at four locations. Clutch size varied from 2.00 to 4.00 eggs, with minimal variation in egg length and width, but greater variability in egg weight, volume, and specific gravity was observed across four locations. Hatching and fledging success rates were more at locations of Punjab state as compared to locations of Haryana state. These findings highlighted the role of agricultural landscapes in sustaining the reproductive and nutritional requirements of the Purple Sunbird and underline its potential contribution to natural pest regulation through insect consumption.